Survival adjusted cancer risks attributable to radiation exposure from cardiac catheterisations in children - Harbron, Richard W (Heart, 2017)
OBJECTIVES: To estimate the risk of developing cancer in relation to the typical radiation doses received from a range of X-ray guided cardiac catheterisations in children, taking variable survival into account. METHODS: Radiation doses were estimated for 2749 procedures undertaken at five UK hospitals using Monte Carlo simulations. The lifetime attributable risk (LAR) of cancer incidence was estimated using models developed by the Biological Effects of Ionising Radiation committee, based on both normal life expectancy, and as a function of attained age, from 20 to 80 years, to take reduced life expectancy into account. RESULTS: The radiation-related risks from these procedures are dominated by lung and breast cancer (for females). Assuming normal life expectancy, central LAR estimates for cancer incidence, based on median doses, ranged from <1 in 2000 for atrial septal defect occlusions to as high as 1 in 150 for valve replacements. For a reduced life expectancy of 50 years, estimated risks are lower by a factor of around 7. For conditions with especially poor survival (age 20 years), such as hypoplastic left heart syndrome, estimated cancer risks attributable to radiation were <1 in 20 000. CONCLUSIONS: Based on recent UK radiation dose levels, the risk of cancer following cardiac catheterisations is relatively low and strongly modified by survival and the type of procedure. The risk of breast cancer, especially following pulmonary artery angioplasty and valve replacements, is the greatest concern.